Orçamento participativo e gestão democrática no poder local - Goulart, Jefferson O. [UNESP] (FapUNIFESP (SciELO), 2006)
The end of the authoritarian regime in Brazil resulted in new forms of democratization of politics and its institutions, with the strenghtening of the civil society. The Participatory Budgeting is an important experience of that new way, characterized by the assumption of the new responsibilities by the local governments. The comparative approach of those experiences, conducted from different party coalitions - in Piracicaba (1989-1992) and in Santa Bárbara d'Oeste (1997-2000) -, allows a test of their powers and limits from a procedural conception of democracy and the complementary role of the participation. In contrast to a view that gives priority to representation, the analysis discusses the range of the new civil society actions from the perspective of the democratization process in the scope of the Local Government. © 2007 CEDEC.
Public budgeting and democracy in local governments
Keywords: Democracy; Local government; Participation; Participatory budgeting